2021
DOI: 10.1177/01430343211039265
|View full text |Cite
|
Sign up to set email alerts
|

Academic self-efficacy and test anxiety in high school students: A conditional process model of academic buoyancy and peer support

Abstract: Based on social cognitive theory and ecological systems theory, this study constructed a conditional process model to explore the relationship between academic self-efficacy and test anxiety as well as underlying psychological mechanisms through academic buoyancy and peer support. A sample of Chinese high school students ( N = 560) completed questionnaires assessing academic self-efficacy, academic buoyancy, peer support, and test anxiety. Structural equation modeling (SEM) revealed an indirect effect of acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 72 publications
1
22
0
1
Order By: Relevance
“…The purpose of this study was to examine the relationships among academic resilience, achievement goals, and cognitive test anxiety in a sample of high school students from Singapore, an East Asian nation. In line with previous research (e.g., Lei et al, 2021; and as hypothesized, our results revealed a significant negative association between academic resilience and cognitive test anxiety. In other words, students who perceived themselves to have the resources to bounce back from the challenges of everyday school life also experienced lower levels of cognitive test anxiety.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The purpose of this study was to examine the relationships among academic resilience, achievement goals, and cognitive test anxiety in a sample of high school students from Singapore, an East Asian nation. In line with previous research (e.g., Lei et al, 2021; and as hypothesized, our results revealed a significant negative association between academic resilience and cognitive test anxiety. In other words, students who perceived themselves to have the resources to bounce back from the challenges of everyday school life also experienced lower levels of cognitive test anxiety.…”
Section: Discussionsupporting
confidence: 93%
“…Findings from one study with Chinese medical students showed that resilience negatively predicted test anxiety (Wang et al, 1994). A more recent study with a sample of Chinese high school students by Lei et al (2021) also showed that academic buoyancy was negatively related to test anxiety.…”
Section: Academic Resilience and Test Anxietymentioning
confidence: 88%
See 2 more Smart Citations
“…As already outlined previously, we therefore prefer to speak of an ‘indirect effect’ via self-efficacy. As other studies show, academic buoyancy can also be seen as a mediator between self-efficacy and outcome measures such as test anxiety (Lei et al, 2021 ). Further studies therefore should aim for longitudinal research on academic buoyancy and self-efficacy so that hypotheses about the directionality of the relation can be generated.…”
Section: Discussionmentioning
confidence: 86%